Politique monétaire non conventionnelle entre le concept et son rôle dans la stimulation de l’économie - Sassi, Mberak; Benchohra, Madani; SOLTANI, Wafa (Finance and Business Economies Review, 2020)
The recent global financial crisis has characterized by the adoption of the major central banks of large-scale unconventional monetary policies to provide the incentives which stimulate demand, these policies that involve a large expansion of central bank assets, long-term interest rate cuts, credit facilities for families and companies, easing quantitative, and interventions in Currency and stock markets, providing liquidity in local and foreign currencies, and monetary policies at zero interest rates, and all these to boost the economic activity.